Investigating the Chaperoning Effect of Nanoparticles in Chemically Denatured zDHFR: An in vitro Study - Gupta, P.; Verma, A.K.; Chaudhuri (Chattopadhyay), P. (Asian Journal of Chemistry, 2021)
Maintenance of native structure and function of the protein is a major concern for industrial production of aggregation prone therapeutically important recombinant proteins. Aggregation may results due to change in the native conformation of proteins under different stress conditions. To overcome the problem of protein aggregation, role of silver and gold nanoparticles have been investigated. The nanoparticles owing to their affirmative interaction with the proteins possess chaperoning activities and protect the native state from denaturation. In the present study, through performing chemical denaturation of zebrafish dihydrofolate reductase using denaturants like guanidine hydrochloride and urea in the presence and absence of gold and silver nanoparticles and monitoring the process through enzyme activity assay and intrinsic tryptophan fluorescence, we have demonstrated the impact of nanoparticles in maintaining native conformation of proteins. Further, the outcome of refolding studies of DHFR protein with nanoparticles monitored by UV-visible spectroscopy was also reported.